Stapled vs. manually sutured bowel anastomosis in robot-assisted radical cystectomy: a single-center retrospective analysis - Thomas Hermans; Giel Schevenels; Steve Motmans; Thomas De Sutter; Yannic Raskin (BMC Urology)
Abstract Background Radical cystectomy is the primary treatment for muscle-invasive bladder cancer and certain cases of high-risk non-muscle-invasive disease. Robot-assisted cystectomy techniques (RARC) have emerged as a minimally invasive alternative to traditional open surgery, offering enhanced precision and potentially improved recovery. Bowel anastomosis remains a critical step in these procedures, with manually sutured anastomosis offering a cost-effective alternative to the standard stapled technique. However, concerns remain regarding its impact on surgical outcomes. Methods We conducted a retrospective study of 92 patients who underwent RARC in our hospital between March 2021 and November 2023. Bowel anastomosis was performed using either stapled (n = 33) or manually sutured techniques (n = 59). Key outcome parameters included gastro-intestinal (GI) complications, overall complications, operation duration, length of hospital stay, readmissions, and postoperative recovery metrics. Results GI complications occurred in 23 patients (25%), with paralytic ileus being the most common (17%). The rates of GI complications were comparable between the manually sutured (27%) and stapled (21%) groups (p = 0.530, odds ratio 1.38). The mean operation duration was 300 min for the sutured group and 313 min for the stapled group (p = 0.124). The median hospital stay was similar at 8 days (p = 0.384) for both groups. Readmission rates were higher in the sutured group (25% vs. 6%, p = 0.022, odds ratio 5.28), but this was predominantly due to non-GI complications. Conclusion This study indicates that outcomes are comparable between stapled and manually sutured bowel anastomosis in RARC, with no significant increase in overall complications, GI complications, operation duration or hospital stay if using a manually sutured anastomosis. Considering the low cost of manual suturing, this technique seems highly cost-effective and could be considered a viable alternative to existing stapling techniques.